Post-transcriptional regulation of alpha-smooth muscle actin determines the contractile phenotype of Dupuytren's nodular cells. - Verjee, L; Midwood, K; Davidson, D; Eastwood, M; Nanchahal, J (2010)
The objective was to study Dupuytren's myofibroblast cells in constrained collagen matrices in order to more closely emulate their in vivo environment and, to correlate their contractility with alpha-smooth muscle actin (alpha-SMA) expression and determine if dermal fibroblasts regulate Dupuytren's myofibroblast phenotype. Isotonic and isometric force contraction by cells isolated from Dupuytren's nodules, palmar and non-palmar skin fibroblasts was measured in collagen matrices. The effect of co-culturing nodule cells with dermal fibroblasts on isometric contraction was examined. Isometric contraction was correlated with levels of alpha-SMA mRNA by pcr and protein by Western blotting, and alpha-SMA distribution assessed by immunofluorescence. Dupuytren's nodule cells exhibited similar levels of isotonic contraction to both palmar and non-palmar dermal fibroblasts. However, nodule cells generated high levels of isometric force (mean: 3.5 dynes/h), which continued to increase over 24 h to a maximum of 173 dynes. In contrast, dermal fibroblasts initially exhibited low levels of contraction (mean: 0.5 dynes/h) and reached tensional homeostasis on average after 15 h (range: 4-20 h), with a maximum force of 52 dynes. Although all three cell types had similar alpha-SMA mRNA levels, increased levels of alpha-SMA protein were observed in nodule cells compared to dermal fibroblasts. alpha-SMA localised to stress fibres in 35% (range: 26-50%) of nodule cells compared to only 3% (range:0-6%) of dermal fibroblasts. Co-cultures of Dupuytren's cells and dermal fibroblasts showed no contractile differences. The contractile phenotype of Dupuytren's myofibroblasts is determined by increased alpha-SMA protein distributed in stress fibres, not by cellular mRNA levels. Dupuytren's cell contractility is not influenced by dermal fibroblasts.